IMPACT OF LOCKDOWN ON INDIAN CONSUMERS’ PSYCHOLOGICAL BEHAVIOUR AND ATTITUDE TOWARDS THE CONSUMPTION OF PACKAGED DAIRY PRODUCTS - Jayant Kumar Ratre, Sujata Joshi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The Novel Corona virus disease is a human affliction caused by SARS-COV-2 and complete lockdown is an alternative to stop the spread of the virus. The aim of this study is to determine the effects of Corona virus disease lockdown on Indian consumers' psychological behaviour and attitude towards the consumption of packaged dairy products in a view of the Theory of Reasoned Action (TRA). The study used an online survey and in-depth interview of selective respondents. The survey collected information of consumers’ behaviour, attitude towards a packed dairy product, their willingness and information needs, to analyse the pattern of buying the packaged dairy product before and during the COVID-19 lockdown and their psychological behaviour behind that. The research method was a phenomenological approach and data were analysed by using MS-Excel software.